Transition metal vacancy and position engineering enables reversible anionic redox reaction for sodium storage - Congcong Cai; Xinyuan Li; Jiantao Li; Ruohan Yu; Ping Hu; Ting Zhu; Tianyi Li; Sungsik Lee; Nuo Xu; Hao Fan; Jinsong Wu; Liang Zhou; et al. (Nature Communications)
Abstract Triggering the anionic redox reaction is an effective approach to boost the capacity of layered transition metal (TM) oxides. However, the irreversible oxygen release and structural deterioration at high voltage remain conundrums. Herein, a strategy for Mg ion and vacancy dual doping with partial TM ions pinned in the Na layers is developed to improve both the reversibility of anionic redox reaction and structural stability of layered oxides. Both the Mg ions and vacancies (□) are contained in the TM layers, while partial Mn ions (~1.1%) occupy the Na-sites. The introduced Mg ions combined with vacancies not only create abundant nonbonding O 2p orbitals in favor of high oxygen redox capacity, but also suppress the voltage decay originated from Na–O–□ configuration. The Mn ions pinned in the Na layers act as “rivets” to restrain the slab gliding at extreme de-sodiated state and thereby inhibit the generation of cracks. The positive electrode, Na0.67Mn0.011[Mg0.1□0.07Mn0.83]O2, delivers an enhanced discharge capacity and decent cyclability. This study provides insights into the construction of stable layered oxide positive electrode with highly reversible anionic redox reaction for sodium storage.